THE LEARNING EFFECTIVENESS OF THE STUDENTS IN SMK 2 NEGERI WONOSARI GUNUNG KIDUL YOGYAKARTA - Acu Sutisna; M Bruri Triyono (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
This study aims to identify the effect of the teacher professionalism and the students' learning motivation on the learning effectiveness of the students in Vocational High School (SMK) Negeri 2 Wonosari. The study used a survey method with ex post facto approach. The population consists of 420 students of SMK 2 Wonosari from the Program of Civil Engineering, Electronic Engineering, Electrical Engineering, Mechanical Engineering, and Automotive Engineering. The sample was selected using random sampling technique. The data is analyzed using Multiple Linear Regression analysis. The results point out that most students’ perceptions on the level of teacher professionalism on productive subjects belongs to medium category, student learning motivation is in medium category, and the student learning effectiveness on productive is categorized into medium category. Teacher professionalism and student motivation have positive impact or is significant on the learning effectiveness of the students.